LEGISLATIVE ENSURING OF ADMINISTRATIVE-LEGAL REGIMES - Гусар, Ольга Анатоліївна; Мандрика, Олександр Павлович; Рустамова, Марія Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: on the basis of current legislation and sources to conduct a research of the legislative ensuring of administrative-legal regimes. Methods: the general-scientific method (analysis and synthesis) allowed analyzing the researchers’ scientific positions on the investigated issue. The system method was used to analyze the structure of administrative-legal regimes. With the help of the logical-legal method the authors’ definition was determined, the formal-legal method allowed establishing the administrative-legal regimes current legislation content. The grouping method and the system-structural approach gave the possibility to classify the administrative-legal regimes. Results: legislative regulation of administrative-legal regimes should be carried out according to the following directions: subjects and objects of a system of regime activity clear definition, its principles; legislative separation of the system of regime activity from other activities that are similar in form and purpose (for example, permitting system, registration of movable and immovable property, etc.); revision of the system of regime bodies that provide it, legislative determination of their exhaustive list and legal status, excluding of parallelism and duplication in the process of exercising their powers. It is necessary to detail the principle of legality in the normative acts of, according to which the system of regime activity may be carried out only: a) by competent authorities (officials); b) within the limits of their regime powers; c) in compliance with the procedures of regime proceedings (terms, forms, methods, etc.), the issuance of certain permissions, prohibitions, prescriptions; the improvement of the legislative determination of regime proceedings; the improvement of legal guarantees mechanism for the protection of human’s and citizen rights and freedoms in the conditions of action (introduction) of administrative-legal regimes. The suggested directions of legislative administrative-legal regimes ensuring may be considered as elements of unified standards that are common to the entire system of the regime activity.